Pemanfaatan Kulit Pisang Hasil Fermentasi Rhyzopus oligosporus dalam Ransum Terhadap Pertumbuhan Ayam Pedaging (UTILIZING OF FERMENTED BANANA PEELS BY RHYZOPUS OLIGOSPORUS IN RATION ON GROWTH OF BROILER) - Koni, Theresia Nur Indah; Bale-Therik, Jublina; Kale, Pieter Rihi (Jurnal Veteriner; Vol 14 No 3 (2013), 2013)
An experiment has  conducted to investigate the effect level of fermented banana peels by Rhyzopusoligosporus   in  ration to growth of broiler. The experiment was designed use Completely RandomizedDesign with four treatments: as a control ration (0%  fermented banana peel); 5% fermented banana peel;10%  fermented banana peel; 15% fermented banana peel, with four replicates. There were six ayampedagings a weeks with average   weight  112.30 ± 2.74 g in each replicate. The result there was a 15%fermented banana peels in broiler ration was not significant (P>0,05)  to feed consumption, but itsignificantly (P<0,01) effected gain, and feed conversion . Fermented banana peels by R. oligosporus couldbe used as much as 10% in broiler ration.
Keywords: banana peel, fermentation, Rhyzopus oligosporus, growth, broiler